Measuring the board’s members effect on banks’ performance: an application to Portugal - Pereira, V. M. M. (2016)
This paper provides a model for analyzing the relationship between boards’ members characteristics and companies performances. In this paper, Portuguese Banks were studied. An index was used to measure the educational qualifications of Banks boards´ members in order to quantify their impact on banks’ performance. Results show that there is a significant influence of education index over banks ROAE but not over banks ROAA.